Subjective Well-Being Analysis of Minang Adolescents Based on Parents' Socio-Economic Status and Gender - Indah Rizki Ramadani; Herman Nirwana (International Journal of Applied Counseling and Social Sciences, 2021)
One of the factors that influence subjective well-being (SWB) is socioeconomic status and gender. This study aims to analyze the differences in SWB of Minang adolescents based on socioeconomic status and gender. The research method used quantitative descriptive comparative with a sample of 182 Minang teenagers (9 people with high socioeconomic status, 76 moderate, and 97 people with low socioeconomic status, or 48 men and 134 women). The instruments used are the Socio-Economic Status List and the SWB Filling List. The data were analyzed using the Kolmogorov Smirnov test and the T test. The results showed that there was no difference in the SWB of Minang adolescents based on the socioeconomic status of their parents and by gender.